Pattern of Utilization of Dental Services in Public Teaching Hospital of Karachi (Medical Forum Monthly, 2024)
Objective: To describe the configuration of consumption of Facilities offered by the Public Teaching Hospital in Karachi.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the OPD of Dr. Ishrat ul Ibad Institute of Oral Health Sciences, Karachi from December, 2011 to June, 2012.Materials and Methods: The preformed questionnaire was distributed in the OPD. A total of 579 patients attending the OPD of the Public Teaching Dental Hospital Dr. Ishrat ul Ibad Institute of Oral Health Sciences.Results: Our study demonstrated that mean were in the age group 20 – 39 yrs. 56.5%, while slightly more than 30 per cent were between the ages 40 – 59 yrs. About 11.9%of the subjects were over 60 years old. However, no significant difference was found between the age groups and the gender (p>O.05).Conclusion: Our study concluded that application of facilities in the people is poor. The mainstream of the people for dental approach were for the treatment of severe symptoms rather than for preventive measures. Motivation and proper awareness are required to use existing services.